Penerapan Penggunaan Bandicam pada Mata Kuliah Pendidikan Pancasila Untuk Peningkatan Hasil Belajar Mahasiswa - Basiroh, Falmatul; Murdiono, Mukhamad (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the implementation and the enhancement of student learning outcomes after applying the bandicam application in the Pancasila Education Course. This study was a qualitative approach with a class action research type. Implementation of the action in two cycles, with one meeting each cycle. This study uses four stages in each cycle: planning, action, observation, and reflection. Data collection techniques through tests and documentation. Data analysis utilized qualitative and quantitative descriptive techniques. The study results show that the bandicam application in the Pancasila Education Course includes initial, core, and closing activities. Student cognitive learning outcomes in cycle I obtained an average of 66.67 percent with 16 people in the complete category, and in cycle II, as many as 21 students with an average of 91.67 percent in the complete category. An increase in student learning outcomes occurred after using the bandicam application.